Cruces Copticæ: sopra alcuni luoghi della versione copta del De anima et resurrectione di Gregorio di Nissa - Ottobrini, Tiziano (Augustinianum, 2022)
The essay points out some loci in the surviving part of the Coptic translation of De anima et resurrectione, written in Greek by Gregory of Nyssa. It shows how the Coptic text can be useful not only for amending the Greek text but also for understanding better the underlying theology of the Alexandrian Church, which promoted the Coptic translation. In this way, a reading of Gregory's fragment will be read for the first time using the Coptic version on its own terms and not merely as a translation of Ancient Greek.